Modulator of VRAC Current 1 Is a Potential Target Antigen in Multiple Sclerosis - Dahl, Johannes Raffael; Weier, Alicia; Winter, Christopher; Hintze, Maik; Rothhammer, Veit; Tsaktanis, Thanos; Proebstel, Anne-Katrin; Neziraj, Tradite; Poessnecker, Elisabeth; Oechtering, Johanna; Kuhle, Jens; Kallmann, Boris-Alexander; et al. (Neurology, Neuroimmunology and Neuroinflammation, 2025)
Background and Objectives Multiple sclerosis (MS) is a chronic immune-mediated demyelinating disease of the CNS. Highlighted by the success of B-cell–depleting therapies such as the monoclonal anti-CD20 antibodies rituximab, ocrelizumab, and ofatumumab, B cells have been shown to play a central role in the immunopathology of the disease. Yet, the target antigens of the pathogenic B-cell response in MS remain unclear. Methods We combined polyclonal B-cell stimulation of peripheral blood mononuclear cells with a human proteome-wide protein microarray to identify target antigens of MS by comparing samples from 20 patients with MS with 9 age-matched and sex-matched healthy controls. Results were verified by enzyme-linked immunosorbent assay (ELISA) in 3 independent validation cohorts (N = 47 patients with MS in remission; N = 20 patients with MS during relapse; N = 25 HCs; N = 30 patients with other noninflammatory neurologic diseases; N = 9 patients with other inflammatory neurologic diseases). Experimental autoimmune encephalomyelitis (EAE) was used as an animal model to evaluate the pathogenicity of the antibodies of choice. Results Our results corroborate the existing concept of a highly diverse autoimmune response in MS. Yet, a significantly elevated antibody response against the membrane protein modulator of VRAC current 1 (MLC1) was noted in B-cell culture supernatants and serum samples of patients with MS. Furthermore, significantly elevated titers to MLC1 were observed in the CSF of patients with neuroinflammatory diseases other than MS. Neurons and astrocytes were identified as the main cell types expressing MLC1 in the brain of a patient with MS. Injection of anti-MLC1 antibodies into mice with EAE led to strong in vivo binding to cerebral cortical neurons and to the death of 4 of the 7 injected mice. Discussion Future studies will have to address the diagnostic and prognostic value of MLC1-specific antibodies in neuroinflammatory disorders such as MS and characterize the functional role of MLC1 expression in neurons and astrocytes. Trial Registration Information The study has been registered in the German Clinical Trials Register (study number DRKS00015528